2013
DOI: 10.12776/ams.v19i4.170
|View full text |Cite
|
Sign up to set email alerts
|

MICRO-HARDNESS EVOLUTION OF Al-ALLOY AA 3004, PROCESSED BY EQUAL CHANNEL ANGULAR PRESSING

Abstract: Equal Channel Angular Pressing (ECAP) is a very interesting method for modifying the microstructure in producing materials with ultrafine grain in sub-micrometer or nanometre range. Experiments demonstrate that these ultrafine structures may exhibit, by comparison with large -grained polycrystals, major differences in some fundamental properties. A nanostructured AA 3004 alloy was used to investigate the evolution of microhardness and microstructure on the cross-sectional plane X, after processing by ECAP at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Earlier reports described the evolution of homogeneity in the alloy Al-6061, where after 6 passes negligible increase in the microhardness is observed [20,22]. However, in our previous work, we have reported that the microhardness (HV) of the alloy A3004 [24] and AA5754 [25] improved with the number of ECAP passes. Also, other authors reported similar results of grain refinement on alloy AA3104 achieved by a hard pressure torsion (HPT) [26,27].…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Earlier reports described the evolution of homogeneity in the alloy Al-6061, where after 6 passes negligible increase in the microhardness is observed [20,22]. However, in our previous work, we have reported that the microhardness (HV) of the alloy A3004 [24] and AA5754 [25] improved with the number of ECAP passes. Also, other authors reported similar results of grain refinement on alloy AA3104 achieved by a hard pressure torsion (HPT) [26,27].…”
Section: Introductionmentioning
confidence: 61%
“…The samples for ECAP treatment were sintered from AA3004 powder of 50 mm grain size in a shape of cylindrical rods with 10 mm in diameter. The preparation was a subject to different studies [16,24,25]. The AA3004 powder material before the sintering contained 97.8% A1, 1.2% Mg and 1% Mn.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to these attractive features, a lot of experimental studies focused on the development of ECAP method have been performed in recent years [24][25][26][27].…”
Section: Equal Channel Angular Pressing (Ecap)mentioning
confidence: 99%
“…The most commonly used alloys for welded constructions are alloys 5052, 5154, 5454, 5083 and 6061. The best filler material for welding that alloys is 4043 (4XXX group) or 5356 (5XXX group) [4][5][6]. The choice of filler material in aluminum welding is an important factor influencing mechanical properties [7][8].…”
Section: Introductionmentioning
confidence: 99%